The Influence of Work Motivation, Organizational Commitment, and Job Satisfaction on Organizational Citizenship Behavior at the Yogyakarta Special Region Manpower and Transmigration Office - Fatinabilah, Galih Anisah; Dwiarti, Rina (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this research is to examine how the DIY Manpower and Transmigration Office's staff members' levels of job satisfaction, organisational commitment, and intrinsic motivation affect their OCB. The study's population included 85 workers selected using saturation sampling, and the research methodology was quantitative. The measuring tool used was a Likert scale. The results of the instrument tests demonstrate that the data is valid and trustworthy, distributed normally, and does not exhibit any signs of heteroscedasticity or multicollinearity. According to the study's results, an individual's level of job satisfaction significantly and positively affects their OCB, although work motivation and organisational commitment do not. At the same time, OCB is positively and significantly impacted by all three factors. This study's findings may help guide future studies and business initiatives aimed at enhancing organisational citizenship behaviour (OCB), which in turn impacts the success of organisations in reaching their objectives.